2004
DOI: 10.1186/1471-2458-4-12
|View full text |Cite
|
Sign up to set email alerts
|

Attrition and bias in the MRC cognitive function and ageing study: an epidemiological investigation

Abstract: Background: Any hypothesis in longitudinal studies may be affected by attrition and poor response rates. The MRC Cognitive Function and Ageing study (MRC CFAS) is a population based longitudinal study in five centres with identical methodology in England and Wales each recruiting approximately 2,500 individuals. This paper aims to identify potential biases in the two-year follow-up interviews.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
129
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(138 citation statements)
references
References 42 publications
7
129
2
Order By: Relevance
“…As a result, there was a substantial reduction in the measured dementia risk when those unavailable for face-to-face study clinic follow-up were excluded. Death was associated with older age, functional dependency, and poor cognition in keeping with previous longitudinal ageing studies 5,6 and also, unsurprisingly, with severity of the initial cerebrovascular event. Because the factors associated with death are similar to those for stroke-related dementia, attrition from death may indirectly lead to underestimation of dementia if subjects die before dementia is ascertained.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…As a result, there was a substantial reduction in the measured dementia risk when those unavailable for face-to-face study clinic follow-up were excluded. Death was associated with older age, functional dependency, and poor cognition in keeping with previous longitudinal ageing studies 5,6 and also, unsurprisingly, with severity of the initial cerebrovascular event. Because the factors associated with death are similar to those for stroke-related dementia, attrition from death may indirectly lead to underestimation of dementia if subjects die before dementia is ascertained.…”
Section: Discussionsupporting
confidence: 88%
“…1 We have previously shown that risks of dementia in the first year after stroke are dependent on case-mix and that baseline selection criteria used in previous studies result in underestimation of stroke-associated dementia. [2][3][4] Bias may also occur in longitudinal studies as a result of selective loss to follow-up, 5,6 and such factors may result in underestimation of the true dementia risk after stroke.7 A better understanding of the effect and reasons for attrition on the measured risk of dementia after transient ischemic attack (TIA) and stroke is required for planning clinical trials and large pragmatic studies and for calculating the true cognitive burden of symptomatic cerebrovascular disease.We undertook a longitudinal population-based study of cognitive outcomes to 5-years after all TIA and stroke to determine the effect of attritional factors (death and loss to follow-up because of refusal or loss to contact) on case-mix and measured dementia risk. Dementia diagnosis was made by study interview in available patients and their informants and by indirect follow-up using hand-searching of primary care and hospital records for nonavailable patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 In agreement with other studies, we found that women in all age cohorts who were current smokers were more likely to become non-respondents. 23,24 Social factors were found to add little once the demographic and health variables had been considered.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a population-based longitudinal study on cognitive function, those who refused to participate in a second wave had lower cognitive abilities. 15 …”
mentioning
confidence: 99%